Aplicación de la tecnología de grupos - Ham, Inyong (My University, 1981)
More and more manufacturing industries involved with small lot size and a variety of products are becoming interested in group technology, wich is particularly applicable in the area of batch-type manufacturing. It has also been recognized that group technology is an essential element of the foundation for the successful development and implementation of computer aided manufacturing through the applications of the part-family concept.
Keywords: current trend; coding systems; standardization; scheduling; nc-gt programming; cost analysis